Otimização da biotransformação de metoprolol por fungos e desenvolvimento de métodos cromatográficos para análise - Schiavon, Daniela Elisabeth Hercules (Universidade Federal de São Carlos, 2016)
The researches in biotransformation and biocatalysis are found widespread in several activities in Chemistry and Biotechnology. The use of microorganisms in biocatalysis and biotransformation process to recycle expired or unused medicines have been the aim of this investigation. Therefore, the fungi Penicillium sp, P. griseoroseum, Aspergilus aculeatus, A. flavus and A. niger have been used to carry out the biotransformation of the drugs Simvastatin, Sodium Mycophenolate, Carbamazepine, Propranolol Hydrochloride and Metoprolol Succinate. Chemometric methods have been applied in this investigation in order to optimize the fermentation processes, extraction procedures and the chromatography parameters. In order to evaluate the fermentation processes, a 24 factorial planning has been applied, whereas for the extraction procedures, an experimental planning for a ternary mixture has been applied. Lastly, an analytical method by HPLC-DAD was optimized in order to quantify a metabolite. A central composite design was carried out in order to do that. The results achieved from the fermentation showed that the variables used in the positive level contributed to the increased production of the substance of interest. According to the central composite design performed to the chromatography parameters, in which the resolution response and retention time were evaluated, the best conditions found were the column rate temperature at 45 °C, 0.1% formic acid, the beginning of phase B at 15% and the flow rate at 0.70 mL/min. Evaluating the economic aspects, it can be concluded that the application of Chemometrics to optimize the stages of fermentation and analytical approach produced an increase of 38.73% in the production of the metabolite of interest, from 171.12 mg/L to 237.4 mg/L, and a 7.5% reduction in the total costs involved. Thus, this work demonstrates that Chemometrics allied with drug biotransformation, such as Metoprolol Succinate via fungi of the genus Penicillium sp., can be used to recover and recycle expired or unused drugs.
Optimization of metoprolol biotransformation by fungi and development of methods for chromatographic analysis
Keywords: Química tecnológica; Microorganismos; Fungos; Biocatálise; Métodos cromatográficos; CIENCIAS EXATAS E DA TERRA::QUIMICA